Cervical Vertebral Trabecular Bone Mineral Density in Great Danes With and Without Osseous‐Associated Cervical Spondylomyelopathy - Armstrong, J. (J Vet Intern Med, 2014)
BACKGROUND: Great Danes (GDs) with osseous‐associated cervical spondylomyelopathy (CSM) have osteoarthritis (OA) of the cervical vertebrae. OA is often associated with increases in bone mineral density (BMD) in people and dogs. HYPOTHESIS/OBJECTIVES: To compare the trabecular BMD of the cervical vertebrae between clinically normal (control) GDs and GDs with osseous‐associated CSM by using computed tomography (CT). We hypothesized that the vertebral trabecular BMD of CSM‐affected GDs would be higher than that of control GDs. ANIMALS: Client‐owned GDs: 12 controls, 10 CSM affected. METHODS: Prospective study. CT of the cervical vertebral column was obtained alongside a calibration phantom. By placing a circular region of interest at the articular process joints, vertebral body, pedicles, and within each rod of the calibration phantom, trabecular BMD was measured in Hounsfield units, which were converted to diphosphate equivalent densities. Trabecular BMD measurements were compared between CSM‐affected and control dogs, and between males and females within the control group. RESULTS: Differences between CSM‐affected and control dogs were not significant for the articular processes (mean = −39; P = .37; 95% CI: −102 to 24), vertebral bodies (mean = −62; P = .08; 95% CI: −129 to 6), or pedicles (mean = −36; P = .51; 95% CI: −105 to 33). Differences between female and male were not significant. CONCLUSIONS AND CLINICAL IMPORTANCE: This study revealed no difference in BMD between control and CSM‐affected GDs. Based on our findings no association was detected between cervical OA and BMD in GDs with CSM.